Response of chickpea varieties to boron application in calcareous and terrace soils of Bangladesh (Bangladesh Journal of Agricultural Research, 2018)
An experiment was conducted at Madaripur and Gazipur during rabi (winter) season of 2012-13 and 2013-14 to determine the optimum dose of B for different varieties of chickpea (Cicer arietinum L.). There were 12 treatment combinations comprising three varieties (BARI Chola-5, BARI Chola-8 and BARI Chola-9) and four levels of boron (0, 1, 1.5 and 2 kg ha-1) along with a blanket dose of N20P20K25S10Zn2 kg ha-1. Boron was applied as H3BO3. Results showed BARI Chola-9 with 1.5 kg B ha-1 produced the highest seed yield of 1338 kg ha- 1 at Madaripur and 2218 kg ha-1 at Gazipur. Nodulation, nitrogen (N) and protein contents were also found highest for the same variety and B treatment. The other two varieties (BARI Chola-5 and BARI Chola-8) also performed higher yield in the plot receiving 1.5 kg B ha-1 compared to 1 kg B ha-1 or 2 kg B ha-1 at both locations. The results suggest that BARI Chola-9 and 1.5 kg B ha-1 along with N20P20K25S10Zn2 kg ha-1 could be used for achieving higher yield of chickpea in calcareous and terrace soils of Bangladesh.Bangladesh J. Agril. Res. 43(4): 543-556, December 2018